Small works management process analysis: case study in an architecture office (Research, Society and Development, 2019)
Due to the high competition in the construction scenario, it is necessary to use tools that help the production optimization, performing planning and control of the work, which aims to reduce the waste and costs of the projects. In addition, the construction industry has high delays, no quality controls and a high rate of material waste. In turn, there is a need to make employees self-manageable, such as the builder, allowing them to make decisions and be autonomous. Thus, this article aims to analyze the principles of Lean Construction in a construction site from the mapping of the processes of a small work in order to propose improvements of the construction system. For this, a case study was carried out, and the information was obtained from the monitoring of the execution of the works, mapping of the current process and subsequent analysis and proposition of a future state. New process flows have been proposed to reduce waste from the principles of LC. Thus, a reference model was presented to be followed by the company in future works with standardized management procedures, and such model can be used by other companies or adapted to their reality.